Soft-copy display and reading: what the radiologist should know in the digital era. - Sorantin E; Sorantin, Erich (Pediatric Radiology, 2008)
The basic scheme of modern medical imaging consists of the following steps: (1) data acquisition, (2) data (image) processing, (3) further data processing by the computer graphic system, (4) image display, and finally (5) visual perception and interpretation. Medical monitors represent a forgotten part of the whole chain. The purpose of this review is to present the key facts about the display technologies used today, as well as their characterization and quality assurance.